IoT-based Epever Tracer 1210 MPPT Monitoring System Using Modbus Communication Protocol - Rohman, Rizky Habibur; Sulistiyowati, Indah; Anshory, Izza; Saputra, Dwi Hadidjaja Rasjid (DPTE FT UNY, 2024)
This research examines the integration of Maximum Power Point Tracking (MPPT) technology with Internet of Things (IoT) and Modbus communication protocols in solar energy systems, with the main objective of increasing efficiency and enabling real-time performance monitoring. The research method used is experimental. The Epever Tracer 1210 MPPT is used to optimize energy absorption from solar panels, while IoT devices are connected via ESP32 using Modbus protocol. Data such as current, voltage, power, and energy generated are collected and analyzed in real-time using the Blynk app. Tests were conducted at three time periods (morning, afternoon, evening) to measure the accuracy and consistency of the data, and the results show that the IoT-based monitoring system provides accurate data, with minimal difference between the data from the MPPT, measuring instruments, and Blynk application. In addition, the integration of Modbus RTU with the IoT platform improves communication efficiency and security. IoT-connected MPPT technology has proven effective in improving operational efficiency and power conversion in solar energy systems, enabling optimal energy absorption in various weather conditions, thereby maximizing energy production. IoT integration also strengthens the real-time remote monitoring system, which is essential for early detection of faults or performance degradation.